How does culture influence corporate risk-taking? - LI, Kai (Institutional Knowledge at Singapore Management University, 2013)
We investigate the role of national culture in corporate risk-taking. We postulate that culture influencescorporate risk-taking both through its effect on managerial decision-making and through its effect on acountry’s formal institutions. Further, we postulate that the influence of culture is conditioned on theextent of managerial discretion as measured by earnings discretion and firm size. Using firm-level datafrom 35 countries and employing a hierarchical linear modeling approach to isolate the effects of firmleveland country-level variables, we show that individualism has a positive and significant association,whereas uncertainty avoidance and harmony have negative and significant associations, with corporaterisk-taking. Greater earnings discretion strengthens and larger firm size weakens the association of culturewith corporate risk-taking. We conclude that even in a highly globalized world with sophisticatedmanagers, culture matters.